2022
DOI: 10.3855/jidc.14832
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of Selenium, Zinc, and Vitamin C and their relation to the clinical spectrum of leprosy

Abstract: Introduction: Leprosy is a chronic infectious disease with many risk factors including inadequate nutrient intake and nutritional deficiencies, which affect the immune system, and influence leprosy progression. Objectives: To elucidate the relation between the serum level of zinc, vitamin C, and selenium and the clinical spectrum of leprosy. Methodology: A case control study included 100 leprotic patients (50 multibacillary and 50 paucibacillary) and 100 age and sex matched controls. Vitamin C was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…By comparing blood serum levels between leprosy sufferers and a healthy control group, Rao et al [37] reported depleted levels of Zn, Ca and Mg but elevated levels of Cu in the leprosy group. Such mineral imbalances in leprosy sufferers were also reported by several other studies (e.g., [14,16,[38][39][40][41][42][43][44]). The depleted Zn levels correlate with an increased bacterial load [45] and not with the presence or absence of leprosy-related skin lesions [46].…”
Section: Mineral Imbalances In Leprosysupporting
confidence: 82%
See 1 more Smart Citation
“…By comparing blood serum levels between leprosy sufferers and a healthy control group, Rao et al [37] reported depleted levels of Zn, Ca and Mg but elevated levels of Cu in the leprosy group. Such mineral imbalances in leprosy sufferers were also reported by several other studies (e.g., [14,16,[38][39][40][41][42][43][44]). The depleted Zn levels correlate with an increased bacterial load [45] and not with the presence or absence of leprosy-related skin lesions [46].…”
Section: Mineral Imbalances In Leprosysupporting
confidence: 82%
“…On the other hand, however, the micronutrients are further depleted during infections by the invading pathogens, while the requirements are increased [13]. Several studies have reported mineral deficiencies or excesses in the blood serum of individuals suffering from leprosy (e.g., [14][15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is also a structural and catalytic component of superoxide dismutase (SOD), which reduces the oxidative effects of ROS, converting superoxide (O2-, +O2-, +2H+) to hydrogen peroxide (H2O2+O) to minimize chain reactions during cell damage. 8,11,18 The correlation analysis of this study found a statistically significant relationship between serum IgM anti PGL-1 and zinc levels in multibacillary leprosy household contact (p=0.033), and high serum zinc levels were a protective factor for high levels of IgM anti PGL-1 in household contacts (PR: 0.47; 95% CI: 0.20-1.09). The high zinc levels have a protective factor of 53% against increased levels of IgM anti PGL-1 in a household contact with leprosy.…”
Section: Original Articlementioning
confidence: 50%
“…The zinc deficiency reduces the cellular immune system because of the low immune response of Th1 lymphocytes due to decreased production of IFN-Ɣ, IL2 and TNF-cytokines that help control intracellular pathogens. 6,8,11 In the spectrum of tuberculoid leprosy, it is said that there is a decrease in zinc levels in the lepromatous spectrum and conditions of erythema nodosum leprosum (ENL), it is said that the decrease in zinc levels is increasing. 12 This study showed a mean level of IgM anti PGL-1 in the household contact of 613.00 with a mean level of IgM anti PGL-1 level in the non-contact person of 99.0.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in serum zinc levels was measured in patients with leprosy (paucibacillary leprosy: 89.86 ± 20.712 μg/dL, multibacillary leprosy: 81.41 ± 18.61 μg/dL, control group: 107.34 ± 3.98 μg/dL), it might present prior to the disease onset due to malnutrition which may have accelerated the development of leprosy. It also might be result from disease pathogenesis or related to the antioxidant based treatment ( 61 ). Reinar et al ( 62 ) summarized three studies of ulcerations caused by nerve damage in leprosy that compared zinc tape with other interventions (magnesium sulfate, povidone-iodine, gauze soaked) and reported results in favor of zinc tape.…”
Section: Infectious Diseasesmentioning
confidence: 99%